Dynamiczno-strukturalna miara rozwoju obiektów hierarchicznych - Strahl, Danuta (Dynamic-Structural Measure of Hierarchical Objects Development, 2006)
The article presents the proposal of extending structural formula of hierarchical objects development measure by dynamic aspects. There were presented hierarchical objects definitions as well as the scope of information necessary for the construction of development measure which takes into consideration internal diversification of hierarchical objects with reference to lower level units in defined time units. The extended formula covers two variants: the first is based on the number of lower level objects included in the given class of a defined level of development, the second considers (instead of the number of objects) the potential of lower level objects included in a given class of a defined level of development. The article also includes an example which illustrate the suggested procedure of hierarchical objects development evaluation. All countries of the European Union constitute hierarchical objects, while the objects of lower level become territorial units of NUTS 2 level - 254 regions. The dynamic-structural development measure was calculated for the years 2001 and 2002, based on the following variables describing regional development:X1 - unemployment rate in 2002 and 2001,X2 - GDP/m in PPS (Purchasing Power Standard) in the years 2002 and 2001,X3 - dynamic indicator of GDP/m in the years 2001-2002 and 1998-2001.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 11-21